Proteomic analysis of tyrosine phosphorylations in vascular endothelial growth factor- and reactive oxygen species-mediated signaling pathway - Kim, Young Mee; Song, Eun Joo; Seo, Jawon; Kim, Hee-Jung; Lee, Kong-Joo (AMER CHEMICAL SOC, 2007)
Vascular endothelial growth factor (VEGF) mediates angiogenic signaling by activating tyrosine kinase receptors. Endothelial cells treated with VEGF are known to increase reactive oxygen species (ROS) production and activate the MAPK pathway. To identify the target proteins of the VEGF receptor, we treated human umbilical vein endothelial cells (HUVECs) with VEGF or H2O2, and identified and semiquantified tyrosine-phosphorylated proteins, combining 2D-gel electrophoresis, Western analysis using antibody against phospho-tyrosine, and mass spectrometry. We detected 95 proteins that were differentially phosphorylated; some were specifically phosphorylated by VEGF but not by H2O2. 2D-gel electrophoresis revealed that heterogeneous populations of the same protein responded differently to H2O2 and VEGF. Bioinformatic studies examining the nature of the differential phosphorylation in various subpopulations of proteins should provide new insights into VEGF- and H2O2-induced signaling pathways.
Keywords: HYDROGEN-PEROXIDE; IDENTIFICATION; ACTIVATION; PROTEINS; VEGF; AUTOPHOSPHORYLATION; DEPHOSPHORYLATION; TRANSLOCATION; RECEPTOR; DOMAINS